Security improvement of aes algorithm using s-box modification based on strict avalanche criterion on image encryption - Topanto, David; Alamsyah, Alamsyah (Journal of Soft Computing Exploration, 2022)
Communication is something that cannot be separated from humans as social creatures. Images are the most commonly used visual communication in today's era. On the other hand, sending images via wireless networks is very vulnerable to piracy. AES, as one of the best cryptographic algorithms, can be applied as a solution. Even so, the AES algorithm still has weaknesses, which are weak against linear attacks and differential cryptanalysis. One solution to overcome the weaknesses of the AES algorithm is to use a stronger S-box. One of the methods to measure the strength of an S-box is the Strict Avalanche Criterion (SAC). The dataset is divided into four categories based on the image type and size of the pixels. Data that has been encrypted using the proposed algorithm will be compared with data that has been encrypted using the standard AES algorithm. Cipherimages (encrypted data) are tested using histogram analysis, information entropy, and sensitivity analysis. The results obtained from cipher image testing are differences in histogram analysis testing in grayscale and color images. The information entropy value is 0.000131583% better than the AES standard, the NPCR is 0.17613% better than the AES standard, and the UACI value. 0.211148% better than AES standard in sensitivity analysis testing. Based on these data, the proposed algorithm has a higher level of security than the standard AES algorithm on image encryption.